Теоретико-методичні засади оцінювання ринкової вартості об'єктів інтелектуальної власності - Перерва, Петро Григорович; Маслак, Марія Володимирівна (Національний університет "Одеська політехніка", 2023)
Розглянуто теоретико-методичні питання вартісного оцінювання об’єктів інтелектуальної власності. Сформовано та обґрунтовано фундаментальні принципи вартісного оцінювання інтелектуальної власності, які тісно корелюють з точністю та об’єктивністю здійснюваної оцінки. Визначено дві базові складові вартісної оцінки інтелектуального продукту – аналітичну та розрахункову, – грамотне поєднання яких дозволяє сформувати науково обґрунтований результат оцінювання. Доведено, що крім ринкової вартості в науковому обігу використовуються і інші значення вартості об’єкту інтелектуальної власності: інвестиційна, страхова, заставна, установча, інвестиційна. Сформовано визначення кожного виду вартості та доведено залежність їх значення від стадії життєвого циклу інтелектуального продукту, вартість якого оцінюється. З використанням процедури колективної експертної оцінки отримано конкретні кількісні результати розрахунків різних видів вартості по стадіям життєвого циклу інтелектуального продукту, в основу яких покладено співвідношення ринкової вартості інтелектуального товару і інших видів вартості інтелектуальної власності.

Theoretical and methodological issues of valuation of intellectual property objects are considered. The fundamental principles of IP valuation have been formed and substantiated, which are closely correlated with the accuracy and objectivity of the assessment. For a better understanding of the significance and scope of use of the principles proposed for practical use, their totality is divided into three characteristic groups: the principles of observing the interests of the right holder of intellectual technology, observing the interests of the consumer, observing the laws of the market economy. Two basic components of the value assessment of an intellectual product have been determined - analytical and calculation - a competent combination of which allows to form a scientifically based assessment result. It has been proven that, in addition to the market value, other values of the value of the object of intellectual property are used in scientific circulation: investment, insurance, collateral, installation, investment, and so on. The structure of the life cycle of an intellectual property object is proposed, which includes six stages. The economic characteristics of each stage of the life cycle are provided. The definition of each type of value was formed and the dependence of their value on the stage of the life cycle of the intellectual product, the value of which is estimated, was proved. With the use of the collective expert assessment procedure, specific quantitative results of calculations of various types of value at the stages of the life cycle of an intellectual product were obtained, which are based on the ratio of the market value of the intellectual product and other types of intellectual property value. Practical recommendations are provided on the possibilities of using the developed methodological recommendations to determine the prospects of possible consumption of an intellectual product at each stage of its life cycle.
Theoretical and methodological principles of evaluating the market value of intellectual property objects
Keywords: інтелектуальна власність; життєвий цикл; вартісна оцінка; співвідношення; ефективність; промислові підприємства; intellectual property; life cycle; valuation; ratio; efficiency; industrial enterprises